2014
DOI: 10.1158/1535-7163.mct-14-0043
|View full text |Cite
|
Sign up to set email alerts
|

Drug Repurposing Identifies a Synergistic Combination Therapy with Imatinib Mesylate for Gastrointestinal Stromal Tumor

Abstract: Gastrointestinal Stromal Tumor (GIST) is a rare and therefore often neglected disease. Introduction of the kinase inhibitor, imatinib mesylate (IM) radically improved the clinical response of patients with GIST; however, its effects are often short-lived, with GISTs demonstrating a median time to progression of approximately two years. Although many investigational drugs, approved first for other cancers, have been subsequently evaluated for the management of GIST, few have greatly impacted the overall surviva… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 41 publications
0
31
0
2
Order By: Relevance
“…These strategies represent an opportunity to rapidly advance and deliver new drug therapies to GIST patients by capitalizing on data readily available. Based on the recent recognition of drug repurposing by Dr. Francis Collins, NIH Director, as a key strategy to accelerate translational research for orphan diseases [134, 135], we and others initiated studies using a dual drug repurposing and rediscovery strategy to provide additional therapeutic options for GIST patients which are proceeding to the clinic [136-138]. In a drug-repurposing screen, we evaluated a library of 796 FDA-approved drugs to determine any potential activity against GIST cell lines [137].…”
Section: Drug Repurposingmentioning
confidence: 99%
See 1 more Smart Citation
“…These strategies represent an opportunity to rapidly advance and deliver new drug therapies to GIST patients by capitalizing on data readily available. Based on the recent recognition of drug repurposing by Dr. Francis Collins, NIH Director, as a key strategy to accelerate translational research for orphan diseases [134, 135], we and others initiated studies using a dual drug repurposing and rediscovery strategy to provide additional therapeutic options for GIST patients which are proceeding to the clinic [136-138]. In a drug-repurposing screen, we evaluated a library of 796 FDA-approved drugs to determine any potential activity against GIST cell lines [137].…”
Section: Drug Repurposingmentioning
confidence: 99%
“…It was found to inhibit the activity of thioredoxin reductase (TrxR) and increase the levels of reactive oxygen species (ROS) leading to the death of GIST cells regardless of the IM resistance status. A subsequent study by our group showed that fludarabine phosphate (F-AMP) exhibits synergy with and/or decreases resistance to IM in IM-resistant GIST cell lines [136]. To confirm the combination's efficacy, an in vivo study was carried out and showed enhanced antitumor activity of the combination compared to IM alone, which makes F-AMP a promising repurposed drug.…”
Section: Drug Repurposingmentioning
confidence: 99%
“…Boichuk Despite a long existing point of view about the low efficacy of chemotherapy for patients with gastrointestinal stromal tumors (GISTs) [1,2], recent data indicates GISTs sensitivity to the certain types of chemotherapeutic drugs. For example, it was shown rather good perspectives of some chemotherapeutic drugs to manage the patients with metastatic and inoperable forms of GIST [3,4]. The results obtained by our research group also demonstrate that some GIST cell lines are sensitive to the topoisomerase type II inhibitors in vitro and in vivo [5,6].…”
mentioning
confidence: 74%
“…Treatment of human osteosarcoma and Ewing sarcoma is complicated, in part due to the lack of prospective, randomized trials beyond first‐line therapy, and there is a clear need for the development of new approaches to improve clinical outcomes . The costs of new drug discovery efforts, particularly for paediatric tumours like osteosarcoma, are often prohibitive, leading to an interest in repurposing existing FDA‐approved drugs if they demonstrate anticancer activity …”
Section: Inroductionmentioning
confidence: 99%